Descriptions, redescription, notes, and new ranks in American Cerambycidae (Coleoptera) - Heffern, Daniel; Nascimento, Francisco E. De L.; Santos-Silva, Antonio (Zootaxa, 2018)
Four new species of Lamiinae are described and illustrated: Estoloides jaliscana (Lamiinae, Desmiphorini), from Mexico (Jalisco); Allotigrinestola nuevoleonis (Desmiphorini), from Mexico (Nuevo Léon); Pogonillus panamensis (Desmiphorini), from Panama; and Phrynidius nayaritensis (Lamiinae, Apomecynini), from Mexico (Nayarit). Drycothaea stictica stictica Bates, 1881 (Lamiinae, Calliini) is redescribed, and notes on it and Drycothaea stictica lepidiota Bates, 1885 are provided. Ornithia mexicana mexicana (Sturm, 1843) (Cerambycinae, Dryobiini) and O. m. zapotensis Tippmann, 1960 are considered distinct species.